L'utilisation de l'intelligence artificielle pour l'individualisation dans l'apprentissage des étudiants en institut universitaire de technologie - Tverdokhliebova, Natalia Evgenievna; Yevtushenko, Nataliіa Serhiivna (OpenEdition Journals, 2026)
The article examines the psychological and pedagogical principles of using artificial intelligence (AI) technologies in the individualization of the educational process of students of technical institutions of higher education. The relevance of the topic is due to the rapid development of digital educational environments, the global challenges of the transformation of education in modern conditions, and the need to create an adaptive model of training engineering specialists. The purpose of this article is to analyze the educational potential of AI in the context of personalized learning, identify the opportunities and advantages of using AI tools for effective integration into the structure of higher technical education, and identify possible limitations and risks associated with this process. The methodological basis of the research is interdisciplinary approaches that include methods of theoretical analysis of scientific sources, digital trends, comparative analysis of adaptive educational platforms (Knewton, Smart Sparrow, ALEKS), as well as empirical analysis and generalization of the experience of implementing AI tools at the National Technical University "Kharkiv Polytechnic Institute". As part of our research, the following results were achieved: the advantages of implementing AI tools in individualizing higher education in psychological, pedagogical, ethical, legal, and technical areas were identified. In particular, the use of adaptive platforms, virtual tutors, chatbots, and GPT-type generative models allows for personalized learning according to the style, pace, level of knowledge, and motivational characteristics of learners. It has been found that the integration of AI promotes the development of reflection, metacognition, soft skills, and increased engagement in learning. At the same time, a number of barriers and risks were analyzed: ethical unregulated use of AI, potential decline in the role of live pedagogical and interpersonal interaction in the educational process, insufficient level of digital readiness of teachers, growing digital inequality, dependence on private companies, technical barriers, and fragmented regulatory support. The main attention is paid to the practical aspects of AI as a tool for shaping individual educational trajectories, automatically monitoring academic progress, supporting microlearning, solving applied problems with the involvement of AI assistants, and ensuring flexible adaptation of educational material to the needs and level of students. A set of practical recommendations for the phased introduction of AI into the educational process is proposed: improving the institutional digitalization strategy, technical audit of the infrastructure, improving the qualifications of teachers, updating the regulatory framework, developing a university code of ethics for the use of AI in the educational environment, interfaculty coordination, strengthening interdisciplinary interaction between technical and pedagogical departments. The conclusions emphasize that the effective implementation of artificial intelligence in individualized learning in higher technical education is possible only if technological solutions are combined with a humanistic approach, digital culture is developed in the academic environment, and technical, pedagogical, and ethical readiness of participants in the educational process is ensured. In the context of individualized learning, AI may not replace, but rather strengthen, pedagogy, provided that it is humanistically oriented. A promising direction for further research is the study of the impact of AI on emotional intelligence, critical thinking, and the formation of students' educational autonomy.

У статті розглянуто психолого-педагогічні засади використання технологій штучного інтелекту (ШІ) в індивідуалізації навчального процесу студентів технічних закладів вищої освіти. Актуальність теми зумовлена стрімким розвитком цифрових освітніх середовищ, глобальними викликами трансформації освіти в сучасних умовах та необхідністю створення адаптивної моделі підготовки фахівців інженерного профілю. Метою даної статті є аналіз освітнього потенціалу ШІ у контексті персоналізованого навчання, визначення можливостей і переваг застосування інструментів ШІ для ефективної інтеграції в структуру вищої технічної освіти, а також виявлення можливих обмежень і ризиків, пов’язаних із цим процесом. Методологічну основу дослідження становлять міждисциплінарні підходи, що охоплюють методи теоретичного аналізу наукових джерел, цифрових трендів, порівняльного аналізу адаптивних освітніх платформ (Knewton, Smart Sparrow, ALEKS), а також емпіричний аналіз і узагальнення досвіду впровадження інструментів ШІ у Національному технічному університеті «Харківський політехнічний інститут». У рамках нашого дослідження було досягнуто наступних результатів: встановлено переваги впровадження інструментів ШІ в індивідуалізації навчання у вищій школі за психолого-педагогічним, етико-правовим і технічним напрямами. Зокрема, застосування адаптивних платформ, віртуальних тьюторів, чат-ботів, генеративних моделей GPT-типу дозволяє забезпечити персоналізацію навчання відповідно до стилю, темпу, рівня знань і мотиваційних характеристик здобувачів освіти. Виявлено, що інтеграція ШІ сприяє розвитку рефлексії, метапізнання, м’яких навичок і підвищенню залученості до навчання. Разом із тим проаналізовано низку бар’єрів і ризиків: етична неврегульованість застосування ШІ, потенційне зниження ролі живої педагогічної та міжособистісної взаємодії в освітньому процесі, недостатній рівень цифрової готовності викладачів, зростання цифрової нерівності, залежність від приватних компаній, технічні бар’єри, фрагментарність нормативного забезпечення. Основна увага приділена практичним аспектам використання ШІ як інструменту для формування індивідуальних освітніх траєкторій, автоматичного моніторингу академічного прогресу, підтримки мікронавчання, розв’язання прикладних завдань із залученням AI-асистентів та забезпечення гнучкої адаптації навчального матеріалу до потреб і рівня студентів. Запропоновано комплекс практичних рекомендацій щодо поетапного впровадження ШІ в освітній процес: удосконалення інституційної стратегії цифровізації, технічний аудит інфраструктури, підвищення кваліфікації педагогів, оновлення нормативної бази, розробка університетського етичного кодексу використання ШІ в освітньому середовищі, міжфакультетську координацію, посилення міждисциплінарної взаємодії між технічними та педагогічними кафедрами. У висновках підкреслено, що ефективне впровадження штучного інтелекту в індивідуалізоване навчання у сфері вищої технічної освіти можливе лише за умови поєднання технологічних рішень з гуманістичним підходом, розвитку цифрової культури в академічному середовищі, забезпечення технічної, педагогічної та етичної готовності учасників освітнього процесу. У контексті індивідуалізації навчання ШІ може стати не заміною, а підсиленням педагогіки – за умови її гуманістичної орієнтації. Перспективним напрямом подальших досліджень є вивчення впливу ШІ на емоційний інтелект, критичне мислення та формування навчальної автономії студентів.
Застосування штучного інтелекту в індивідуалізації навчання студентів технічних вищих навчальних закладів
Keywords: individualization of learning; artificial intelligence; adaptive learning; personalization of education; benefits of AI; risks of AI; digitalization of education; індивідуалізація навчання; штучний інтелект; адаптивне навчання; персоналізація освіти; переваги ШІ; ризики ШІ; цифровізація освіти